Stanisław Dunin–Borkowski and his views on Einstein’s special theory of relativity - Rodzeń, Jacek (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
The main purpose of this article is to discuss the views of the Jesuit Stanisław Dunin–Borkowski (1864–1934) about Albert Einstein’s theory of relativity. These days, Dunin–Borkowski is a rather obscure figure despite rising to fame in the interwar period as an outstanding expert in the philosophy of Baruch Spinoza. Thus, the secondary aim of this article is to remind ourselves of this somewhat forgotten scholar. As a researcher, writer, and pedagogue, Dunin–Borkowski was interested in numerous fields of knowledge. Among these were the natural sciences, including physics and the influence that new physical theories had on philosophical thought. This present study therefore fills a gap in the existing research about how Polish philosophers received Einstein’s theories. The example of Dunin–Borkowski also serves as a basis for discussing some of the fundamental problems of neo-scholasticism in receiving new mathematicised scientific theories.